Behavior and informal learning at night in a 24-hour space: A case study of the Hong Kong Design Institute Library. (March 2019) - Yip, Terry; Chiu, Dickson K.W.; Cho, Allan; Lo, Patrick
This study explores the evening activities of students at the Hong Kong Design Institute in Zone24, a 24-hour opening learning space managed by Hong Kong Design Institute Learning Resources Centre, also referred to as the Library. In doing so, the purpose of this study is to evaluate the effectiveness of 24-hour learning spaces. Qualitative research was undertaken to identify and compare the students' behaviors between daytime and night in Zone24. In addition, this study investigates how overnight activities in the learning spaces facilitate a student's learning. The result of this study can contribute to improving librarians' or administrators' understanding of students' needs at night in a 24-hour learning space in order to implement more effective programs and services for users.